Answer:
(-4,9)
Step-by-step explanation:
substitute the given value for y into the first equation
x-5(-2x+1)=-49
distribute
x+10x-5=-49
add like terms
11x-5=-49
add 5 to both sides
11x=-44
divide both sides by 11
x=-4
now plug x into into the second equation
y=-2(-4)+1
y=8+1
add like terms
y=9
Answer:
Step-by-step explanation:
-2x + 7(1/2) =15
-4x +7 =30
-4x =23
x=-23/4
If x and 71 degrees are side by side, it can be a complementary if it is exactly 90 degrees, supplementary if it is 180 degrees....
Assuming this is some kind of modular question, maybe mod 17.
since 1+8+9=1, we can say that 8+9=0
therefore, 2+0=x, so x=2
Answer:
Options (3), (4) and (5)
Step-by-step explanation:
1). a² - 9a + 7ab + 63b
= a(a - 9) + 7b(a + 9)
Now we can not solve this problem further.
Therefore, can't be factored by grouping.
2). 3a + 4ab - b - 12
= a(3 + 4b) - 1(b - 12)
We can't solve it further.
Therefore, can't be factored by grouping.
3). ab + 6b - 2a - 12
= b(a + 6) - 2(a + 6)
= (b - 2)(a + 6)
We can be factored this expression by grouping.
4). x³ + 9x²+ 7x + 63
= x²(x + 9) + 7(x + 9)
= (x² + 7)(x + 9)
Therefore, the given expression can be factored by grouping.
5). ay² + a - y² - 1
= a(y² + 1) - 1(y² + 1)
= (a - 1)(y² + 1)
This expression can be factored by the grouping method.
Options (3), (4) and (5) are the correct answers.